Minorities, peoples, and self-determination : essays in honour of Patrick Thornberry - Ghanea-Hercock, Nazila; Xanthaki, Alexandra; Thornberry, Patrick (Martinus Nijhoff Publishers, 2005)
The present volume, in honour of Professor Patrick Thornberry, presents new thinking on minority and indigenous rights in international law. Contributors to this 17 chapter volume include an impressive range of academics, thinkers, practitioners and international civil servants with a number of different approaches to this complex area. Not all of them take a legal approach, and this exploration benefits from the variety of frameworks utilised in contributing to the controversial area of minority and indigenous rights. Debates that receive attention in this volume include self-determination, definitional issues, collective rights and rights to natural resources. Other chapters unravel challenges that have not attracted sufficient attention to date, such as multiculturalism, integration, colour as a ground for discrimination and the economic and social rights of minorities. The volume also looks critically at the work of the World Bank, the African Union, the Council of Europe and the OSCE in this arena. Finally, case studies highlight the regrettable similarities in the suffering of groups in different parts of the world as well as the stark contrast between state claims and their actual practice. The contributors are: Gudmundur Alfredsson, Michael Banton, Joshua Castellino, Erica-Irene A. Daes, Maria-Amor Estebanez, Nazila Ghanea, Geoff Gilbert, Bulent Gokay, Tom Hadden, Dominic McGoldrick, Timothy Murithi, John Packer, Chandra K. Roy, Malcolm N. Shaw, Martin Scheinin, Sia Spiliopoulou Akermark, and Alexandra Xanthaki.